Dari Mazhab Padang Ke Mazhab Bandung: Menelaah Pergeseran Paradigma Model Layanan Bimbingan dan Konseling di Indonesia - Nurismawan, Ach. Sudrajad; Rahmawati, Septia (JURNAL KONSELING GUSJIGANG, 2025)
By borrowing the concept of Thomas S. Khun's paradigm shift analysis, this article aims to critically examine the paradigm shift of guidance and counseling (BK) science in Indonesia over the past two decades, especially the 17+ pattern guidance and counseling model introduced by the Guidance and Counseling study program at Universitas Negeri Padang (Padang School) with the comprehensive guidance and counseling model popularized by the Guidance and Counseling study program at the Universitas Pendidikan Indonesia (Bandung School). The analysis results found that openness to local wisdom values and the presence of a legal basis for the implementation of guidance and counseling in Indonesia have encouraged a shift in the paradigm of the BK service model from the 17+ pattern to comprehensive. Comprehensive Guidance and Counseling is considered more systematic and lightens the work of school counselors to develop and evaluate programs that have been prepared. In the future, there may be a paradigm shift in the guidance and counseling service model, especially the emergence of other new Schools (Malang, Semarang, and Yogyakarta) that offer responses to changes and needs of the times based on the research results of each institution.